Etika Jurnalistik Perspektif Pancasila - susanti, mimah; M. Iqbal Nur Aulia Fazri; Hermansah, Tantan; Muhammad Fanshoby (Program Studi Komunikasi dan Penyiaran Islam, 2024)
Pancasila is the basic philosophy in the national and state life of the Indonesian people. At a time when information is developing more rapidly, what emerges is that ethics in news writing or journalism should include the values contained in Pancasila as moral/ethical values in news writing. This research examines Pancasila as a basic philosophy in realizing the ethics of news writing/journalism based on the theoretical assumptions of Alfred Schutz (1899-1959). The research results confirm that the socialization of Pancasila values has two contexts, namely experienced reality and social conditions. In the Almighty God and Just and Civilized humanity, this includes the reality experienced on the ground. In the unity of Indonesia, the people are led by wisdom in representative deliberations and social justice for all Indonesian people, including the social conditions that exist on the ground.